2013
DOI: 10.1088/1742-6596/409/1/012234
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic rays and thunderstorms at the Tien-Shan mountain station

Abstract: The bursts of high energy events observed by the telescope array surface detector R.U. Abstract. Experimental work of the past few years has shown that runaway breakdown determines the maximum electric field strength in thunderclouds and is behind a variety of phenomena newly observed in thunderstorm atmosphere, such as TGFs, TLEs, etc. The necessary condition for the occurrence of runaway avalanche is the existence of high-energy electrons. In the atmosphere, these are the cosmic ray secondary electrons. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In some previous works [e.g., Torii et al ., ; Gurevich et al ., ] radiation was measured at altitudes of more than 3000 m that would explain the lack of long lasting bursts (especially gamma ray) associated with lightning or longer gradual variations associated with thunderstorms. In Torii et al .…”
Section: Background Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In some previous works [e.g., Torii et al ., ; Gurevich et al ., ] radiation was measured at altitudes of more than 3000 m that would explain the lack of long lasting bursts (especially gamma ray) associated with lightning or longer gradual variations associated with thunderstorms. In Torii et al .…”
Section: Background Radiationmentioning
confidence: 99%
“…In some previous works [e.g., Torii et al, 2009;Gurevich et al, 2013] radiation was measured at altitudes of more than 3000 m that would explain the lack of long lasting bursts (especially gamma ray) associated with lightning or longer gradual variations associated with thunderstorms. In Torii et al [2008], the authors pointed out that the increase of gamma-ray dose measured at sea level has only been observed during winter storms and never during summer storms.…”
Section: Background Radiationmentioning
confidence: 99%
“…It has been proposed that NBPs are caused by the development of a conductive channel with the help of Relativistic Runaway Electron Avalanches seeded by cosmic ray air showers, called the RREA‐EAS model, also referred to as the Runaway Breakdown‐EAS model [ Gurevich et al , , ; Gurevich and Zybin , ; Gurevich et al , , ]. We know that when high‐energy cosmic ray particles (e.g., electrons, positrons, and muons) travel through a region of atmosphere in which the ambient electric field is greater than the runaway electron avalanche threshold, they would act as seed particles for Relativistic Runaway Electron Avalanches (RREAs) [ Gurevich and Zybin , ].…”
Section: Review Of Cid Modelsmentioning
confidence: 99%
“…Even if long TGEs have been observed in different situations, they have always been associated with thunderstorms. TGEs have been detected at altitudes above 2500 m [ Torii et al , ; Tsuchiya et al , ; Chilingarian et al , , ; Chilingarian and Mkrtchyan , ; Gurevich et al , ], at sea level associated only with winter thunderstorms [ Torii and Sugita , , ], by balloons [ Parks et al , ] and airplanes [ Eack et al , ]. Simulations [ Babich and Loiko , ] have shown that long TGEs are produced inside tropospheric thunderclouds by RREAs of secondary cosmic rays with the source located at 0.5–2 km within the region between the main negative charge and the lower positive charge layer (LPCL), both for those observed at sea level and for those observed at mountain tops [ Chilingarian , ].…”
Section: Introductionmentioning
confidence: 99%